AB100. Phenotypes of primary hyperlipidemia in a Vietnamese referral center - Nguyen, Khanh Ngoc (Ann Transl Med, 2015)
BACKGROUND AND OBJECTIVE: Primary hyperlipidemia is genetic dyslipoproteinemia. Without any intervention, cardiovascular diseases and acute pancreatitis may be occurred. Detection and appropriate management of pediatric hyperlipidemia can have a significant impact upon the disease course and can prevent complications. The article aims to describe the clinical and biochemical characteristics of hyperlipidemia in Vietnamese children and to evaluate outcome of treatment. PATIENTS AND METHODS: From 2007 to 2013, 30 children were diagnosed with primary hyperlipidemia using included and excluded criteria and were treated with diet and/or lipid-lowering drug therapy. RESULTS: Among 30 cases from 28 families, 8 patients were mixed hyperlipidemia (MHL), 13 patients were hypertriglyceridemia (HT) and 9 patients were hypercholesterolemia (HC). Mean age of diagnosis was 5.5 years (1 months-16 years). The rate of male/female was 13/17. Clinical manifestations included hepatomegaly (4 cases), xanthemas in the knees and elbows (5 cases), “creamy” blood (21 cases). Twenty cases were asymptomatic. A total of 8/28 patients had family history with hyperlipidemia and cardiovascular diseases. Serum cholesterol level of HC group was 9.2±4 mmol/L. Serum triglyceride level of HT group was 23.6±9.9 mmol/L. MHL group had hypercholesterolemia (12.1±4.5 mmol/L) and HT (20.3±10.5 mmol/L). After interventions, HT group had the best result with serum triglyceride level was 10.1±4.6 mmol/L, next to MHL group with serum cholesterol level was 5.8±1.8 mmol/L, and serum triglyceride level was 9.5±5.2 mmol/L; finally, serum cholesterol level of HC group was 12.4±5.5 mmol/L. Five infants with HT had the best results of treatment: serum triglyceride level decreased from 19-57.6 to 5-10 mmol/L. Two patients with HC had the worsen results (unchanged blood lipid level). CONCLUSIONS: Primary hyperlipidemia had poor clinical manifestations and good results of treatment. Screening for primary hyperlipidemia help to prevent premature cardiovascular diseases.